Ambivalence in the Kierkegaardian Conception of Angest - Grigas, Justinas (Problemos, 2021)
The paper considers two problems related to the interpretation of S. Kierkegaard’s conception of Angest. Firstly, a tendency to interpret Kierkegaard’s Angest as a “fear without an object” and to posit its similarity to Heidegger’s Angst is put in question. Questioning this interpretation, an analysis of The Concept of Anxiety is undertaken, in order to reveal ambivalence as the primary feature of Kierkegaard’s conception of Angest. Secondly, the question of translating Angest into Lithuanian is addressed, criticizing the established tradition of translating Angest as “baimė” (fear) and supporting translator’s I. Tomaševičiūtė’s choice of “nerimas”. The aforementioned ambivalence of Angest serves as the basis for the critique, revealing Angest as a paradoxical attraction to that, which frightens. The first part of the paper expounds on the moment of ambivalence in the descriptions of Angest, found in The Concept of Anxiety. The second part compares and underlines the differences between the philosophical approaches of Kierkegaard and Heidegger. It is shown that Kierkegaard’s attention to the ambivalence of Angest is related to the practical bent of Kierkegaard’s philosophy and the problematics of personal individuation.
Keywords: Kierkegaard; Angest; anxiety; fear; ambivalence